MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS 2 PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI MEDIA INTERAKTIF DI SD INPRES BUMI SAGU - Muh Rizal; Ni Kadek Sri Mertasari; Sin Dinayanti Laudea (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Research This research aims to improve the learning motivation of second-grade students in Pancasila Education learning through the application of Interactive media. This research uses the Classroom Action Research (CAR) method which is implemented in two cycles, where each cycle includes the planning, implementation, observation, and reflection stages. The subjects of the research were second-grade students of SD Inpres Bumi Sagu. Data were collected through observation and interviews, then analyzed descriptively qualitatively and quantitatively. The indicator of the success of this research is the achievement of high learning motivation in 80% of students. The results of the study showed that the use of interactive media significantly increased students' learning motivation. At the pre-cycle stage, the average student learning motivation only reached 47%. After the application of digital technology media in Cycle I, the average motivation increased to 71%. Further improvements were seen in Cycle II, with an average learning motivation reaching 91%. Each indicator of motivation, including active involvement in learning, passion and desire to learn, response to feedback, persistence in completing tasks, and enthusiasm for the material, showed a consistent increase from the pre-cycle to Cycle II. In conclusion, the application of interesting and innovative interactive media has proven to be effective in increasing students' learning motivation in Pancasila Education learning. This study recommends teachers to use interactive media more often in teaching and learning activities, as well as school support to provide adequate facilities. Further research is recommended to explore the long-term impact of interactive media use on student learning achievement.